Realisasi Tindak Kesantunan Komisif Dan Daya Pragmatik Dalam Terjemahan Alquran - Santoso, Puji; , Prof. Harun Joko Prayitno, M.Hum (2017)
The purpose of this study is to describe a form of politeness commissive speech in the Quran and the purpose pragmatik power. Research was conducted on the speech in the Quran which is the speech in class commissive according Searly, namely speech promised and threatened. The method used in this research is descriptive kuialitatif method, as well as using fixed strategy (embedded research). Data collection techniques in this study using the technique see and record. There are two things that are the result of research politeness and pragmatic power that consists of 71 datas. 1) A form of politeness commissive speech transcription of the Quran contains two types of utterances, the speech promised and threatened Each consists of 27 datas or speech promised 38% and 44 datas or 62% of utterances threatening; 2) Power of commissive pragmatic speech in the transcription of the Quran consists of two power, namely the power to rule as much as 27 or 38% of datas and power prohibits the data as much as 44 datas or 62%. Keywords: politeness, pragmatic power, transcription of the Alquran.